An Improved Design for Flow Conditioning in Waste Water Pipes - Adam Lyndsell; James M. Buick (Waste, 2023)
In practical applications, waste water piping includes elbows and bends which give unrepeatable, asymmetric and swirling flow profiles, which result in flow meter inaccuracy. Flow conditioners can be inserted into the pipe network to remove these flow patterns prior to a flow meter, to improve the accuracy of the measurement and to reduce the length of straight-run which would otherwise be required. In this investigation, a new design of flow conditioner is considered in two configurations, with and without vanes. The performance of the conditioner is considered by exposing it to a swirling flow that was disturbed by two 90° bends. The flow downstream of the conditioner was simulated using CFD software STAR-CCM+ 12 to find the downstream axial velocity profile, swirl angle and pressure drop. The vane-less conditioner provided a suitable axial profile for flow measurement 2D downstream, at which point the swirl was removed. This illustrated the improved performance compared to other conditioners in the literature, but came at the price of a somewhat higher pressure drop. The addition of vanes improved the performance slightly in terms of regulating the flow and removing swirl, while at the same time increasing the pressure drop further.